An Association between Carpal Tunnel Syndrome and Migraine Headaches—National Health Interview Survey, 2010. Issue 3 (March 2015) - Law, Huay-Zong; Amirlak, Bardia; Cheng, Jonathan; Sammer, Douglas M.
<x xml:space="preserve">Abstract</x> Background: Migraine headaches have not historically been considered a compression neuropathy. Recent studies suggest that some migraines are successfully treated by targeted peripheral nerve decompression. Other compression neuropathies have previously been associated with one another. The goal of this study is to evaluate whether an association exists between migraines and carpal tunnel syndrome (CTS), the most common compression neuropathy. Methods: Data from 25, 880 respondents of the cross-sectional 2010 National Health Interview Survey were used to calculate nationally representative prevalence estimates and 95% confidence intervals (95% CIs) of CTS and migraine headaches. Logistic regression was used to calculate adjusted odds ratios (aORs) and 95% CI for the degree of association between migraines and CTS after controlling for known demographic and health-related factors. Results: CTS was associated with older age, female gender, obesity, diabetes, and smoking. CTS was less common in Hispanics and Asians. Migraine was associated with younger age, female gender, obesity, diabetes, and current smoking. Migraine was less common in Asians. Migraine prevalence was 34% in those with CTS compared with 16% in those without CTS (aOR, 2.60; 95% CI, 2.16–3.13). CTS prevalence in patients with migraine headache was 8% compared with 3% in those without migraine headache (aOR, 2.67; 95% CI, 2.22–3.22). Conclusions: This study is the first to demonstrate an association between CTS and migraine headache. Longitudinal and genetic studies with physician verification of migraine headaches and CTS are needed to further define this association.